Meningkatkan Kemampuan Siswa SLTP dalam Mengemukakan Pendapat dalam Mata Pelajaran PPKn - Sadiyo Sadiyo (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
This classroom action research (CAR) aimed to improve students' ability in expressing their opinion in the PPKn class. It involved 96 students of the SLTP I Malang. The cycle model was implemented in this CAR. This study was able to improve students' ability in expressing their opinion. It enriched learning materials by utilizing school environment, textbooks, current events or issues, and strategies maximizing multimethods and multimedia use. The CAR improved the students' ability qualitatively and quantitatively.